Designing Standard Operation Procedure to Produce Environmentally Friendly Liquid Detergent - Hayati Mukti Asih; Tatbita Titin Suhariyanto; Muhammad Candra Ramadhan (OPSI, 2022)
Washing clothes is an activity that is often done by people in the world. However, detergents sold in the market are harmful to human skin and aquatic ecosystems in rivers. Therefore, this research focuses on environmentally friendly detergents that can minimize the impact on the environment and humans. This study aims to develop standard operating procedures (SOP) in the production of environmentally friendly detergents. This was conducted by developing the initial SOP design, simulating the initial SOP, and identifying problems. Then, followed by improving, designing, and simulating the final SOP. The results of this study acquire SOP that generates products with better consistency and quality.